Javanese Names during the Height of the Hindu-Buddhist Kingdoms in Java: An Ethnolinguistic Study (KEMANUSIAAN The Asian Journal of Humanities, 2013)
Javanese names have undergone numerous developments throughout the course of human civilisation. The study of names is an important means of discovering the desires, cultural tastes and lifestyles of the Javanese from one period to another. This study used a qualitative descriptive research method. The data for the research were obtained from Indonesian historical sources, the story of Babad Tanah Jawa, epigraphs and selected informants. The techniques used to collect the data were content analysis and interviews with a number of historical and language experts. The analysis resulted in a description of the development of the form and structure of Javanese names. Based on the historical context, these names were strongly influenced by the Sanskrit language of the centuriesold Hindu and Buddhist traditions in India. The influence of the ancient Javanese language on Javanese names began to appear at the beginning of the Javanese Hindu era, along with a decline in the Hindu-Buddhist influence in Java. This influence was marked by the appearance of elements in names that do not exist as syllables in Sanskrit. This phenomenon indicates an acculturation of the Javanese, Hindu and Buddhist cultures. Ancient Javanese influences are still found today in modern Javanese names, such as in the use of the names Dyah, Jaya, Dewi/Devi, Wardhana, Arya and Rangga.